Language and the Circuits of Power in a Merging Multinational Corporation - Vaara, Eero; Tienari, Janne; Piekkari, Rebecca; Säntti, Risto (Journal of Management Studies, 2005)
abstract We argue in this paper that corporate language policies have significant power implications that are easily overlooked. By drawing on previous work on power in organizations (Clegg, 1989), we examine the complex power implications of language policy decisions by looking at three levels of analysis: episodic social interaction, identity/subjectivity construction, and reconstruction of structures of domination. In our empirical analysis, we focus on the power implications of the choice of Swedish as the corporate language in the case of the recent banking sector merger between the Finnish Merita and the Swedish Nordbanken. Our findings show how language skills become empowering or disempowering resources in organizational communication, how these skills are associated with professional competence, and how this leads to the creation of new social networks. The case also illustrates how language skills are an essential element in the construction of international confrontation, lead to a construction of superiority and inferiority, and also reproduce post‐colonial identities in the merging bank. Finally, we also point out how such policies ultimately lead to the reification of post‐colonial and neo‐colonial structures of domination in multinational corporations.